The Impact of International Mobility on Intercultural Competency among University Students - Rafli Arya Priananto; Inez Galuh Destyara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study examines the influence of international mobility programs on the development of intercultural competency in university students. Through a mixed-methods approach, data was collected from participants across several mobility programs to understand changes in attitudes, awareness, and skills relevant to intercultural communication. Findings indicate that students with international exposure show higher adaptability, cultural sensitivity, and openness compared to their peers. The research suggests that well-structured mobility experiences can significantly enhance students' readiness to work in global settings.